2020
DOI: 10.1186/s12913-020-05197-3
|View full text |Cite
|
Sign up to set email alerts
|

Confidence, attitudes, beliefs and determinants of implementation behaviours among physiotherapists towards clinical management of low back pain before and after implementation of the BetterBack model of care

Abstract: Background: Implementing clinical guidelines is challenging. To facilitate uptake, we developed a model of care (BetterBack Model of Care) and an implementation strategy to support management of low back pain in primary care. The aim of this study was to evaluate physiotherapists´confidence, attitudes and beliefs in managing patients with low back pain before and after a multifaceted implementation of the BetterBack Model of Care. A further aim was to evaluate determinants of implementation behaviours among ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 57 publications
3
39
0
Order By: Relevance
“…The overall facilitating role of most domains of the DIBQ-t was also reported in a Swedish study using the same questionnaire. 33 The current study findings were also in concordance with a recent implementation study in the context of LBP, which identified knowledge, beliefs about capabilities, and beliefs about consequences as relevant to implementing an online training program with a cognitive behavioral approach for LBP. 34 However, contrary to our investigation, social influences were identified as a relevant factor in two previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…The overall facilitating role of most domains of the DIBQ-t was also reported in a Swedish study using the same questionnaire. 33 The current study findings were also in concordance with a recent implementation study in the context of LBP, which identified knowledge, beliefs about capabilities, and beliefs about consequences as relevant to implementing an online training program with a cognitive behavioral approach for LBP. 34 However, contrary to our investigation, social influences were identified as a relevant factor in two previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Along with the study, Schröder et al (2020) al., 2006). Therefore, it is recommended for the managers and physiotherapists to build relationships and communicate at the organizational level.…”
Section: Low Self-confidence Of Physiotherapists Toward Their Professionalismmentioning
confidence: 83%
“…The success of implementation is complex and multifactorial concerning both clinicians and patients [ 32 , 41 – 43 ]. This present study contributes with knowledge on one of these aspects, attendance.…”
Section: Discussionmentioning
confidence: 99%